Comprehensive association analysis of nine candidate genes with serum 25-hydroxy vitamin D levels among healthy Caucasian subjects - Bu, Feng-Xiao; Armas, Laura; Lappe, Joan; Zhou, Yu; Gao, Guimin; Wang, Hong-Wei; Recker, Robert; Zhao, Lan-Juan (Human genetics, 2010)
Vitamin D deficiency is a common public health problem in the US. It is related to the high risk of rickets, osteoporosis and other diseases. Currently, serum 25-hydroxy vitamin D [25(OH)D] concentration is the best indicator of vitamin D status, and determination of its deficiency or sufficiency. This level has high heritability (28-80%). However, genes contributing to the wide variation in serum 25(OH)D are generally unknown. In this study, we screened nine important genes in vitamin D metabolic pathways using 49 single nucleotide polymorphism (SNP) markers in a group of 156 unrelated healthy Caucasian subjects. Significant confounding factors that may affect serum 25(OH)D variations were used as covariates for the association analyses. An association test for quantitative trait was performed to evaluate the association between candidate genes and serum 25(OH)D levels. Permutation was conducted for correcting multiple testing problems. Evidence of association was observed at SNPs in the CYP2R1 (cytochrome P450, family 2, subfamily R, polypeptide 1) and the GC (vitamin D binding protein) gene. Next, we performed a replication study for six promising SNPs in the gene CYP2R1 and GC, using another group of 340 unrelated healthy Caucasian subjects. Association analyses were conducted in the replication cohort (n = 340) and the pooled cohort (n = 496). The CYP2R1 gene and the GC gene remain significant in the pooled cohort. The results suggest that the CYP2R1 and GC genes may contribute to the variation of serum 25(OH)D levels in healthy populations.